Teacher Understanding in Implementing Independent Curriculum at Junior High School in Manokwari, West Papua - Sahid, Suardi; Murianty, Riana; Sareng, Irvandi Benediktus (JULIET: Journal of English Language and Literature, 2024)
The purpose of this research is to find out how the teachers understand and also the challenges they face in implementing the Independent Curriculum, to find out what the understanding and challenges faced by teachers at SMP Negeri 01 Manokwari in implementing the independent curriculum. The author uses qualitative research. The data sourceused was the results of interviews with teachers at SMP Negeri 01 Manokwari. Interviews were conducted with 5 teachersselected using purposive sampling. From the data obtained by researchers after interviewing the teachers, it wasdiscovered that the teachers understood the independent curriculum and also faced challenges such as the transition fromthe old curriculum, misconceptions, facilities and infrastructure and management.